Меню

УСЛОВИЕ:
Найдите интеграл \( \int\frac{dx}{2sinx-cosx +5} \)


РЕШЕНИЕ:

Замена переменной
$$ tg \frac{x}{2}=t $$
Тогда
$$ sinx= \frac{2t}{1+t ^{2} }; \\ cosx= \frac{1-t ^{2} }{1+t ^{2} } ; \\ dx= \frac{2dt}{1+t ^{2} } $$
Подынтегральная дробь примет вид:
$$ \frac{dx}{2sinx-cosx+5}= \frac{ \frac{2dt}{1+t ^{2} } }{2\cdot \frac{2t}{1+t ^{2} }- \frac{1-t ^{2} }{1+t ^{2} }+5 } = \\ = \frac{2dt}{4t-1+t ^{2}+5+5t ^{2} }=\frac{2dt}{6t ^{2}+4t+4 }= \frac{dt}{3t ^{2}+2t+2 } $$
Выделим полный квадрат в знаменателе:
$$ 3t ^{2}+2t+2=3(t ^{2}+ \frac{2}{3}t+ \frac{2}{3})=3(t ^{2}+2\cdot t\cdot \frac{1}{3}+ \frac{1}{9}- \frac{1}{9}+ \frac{4}{9})= \\ = 3(t+ \frac{1}{3}) ^{2} +3\cdot \frac{3}{9}=3(t+ \frac{1}{3})x^{2}+1=3((t+ \frac{1}{3}) ^{2} + \frac{1}{3}) $$
Итак,
$$ \int\limits { \frac{dt}{3((t+ \frac{1}{3}) ^{2}+ \frac{1}{3})} } = \frac{1}{3} \int\limits { \frac{d(t+ \frac{1}{3}) }{(t+ \frac{1}{3}) ^{2}+ \frac{1}{3} } } = \frac{1}{3}\cdot \frac{1}{ \sqrt{ \frac{1}{3} } } arctg \frac{t+ \frac{1}{3} }{ \sqrt{ \frac{1}{3} } }+C = \\ = \frac{ \sqrt{3} }{3}arctg( \sqrt{3}tg \frac{x}{2}+ \frac{ \sqrt{3} }{3}) +C $$






Похожие примеры: